Maduramicin induces cardiotoxicity via Rac1 signaling‐independent methuosis in H9c2 cells. Issue 12 (22nd April 2021) - Gao, Xiuge; Ji, Chunlei; Wang, Junqi; Song, Xinhao; Zuo, Runan; Zhang, Jingjing; Chen, Xiaorong; Ji, Hui; Peng, Lin; Guo, Dawei; Jiang, Shanxiang
Abstract: Maduramicin frequently induces severe cardiotoxicity in target and nontarget animals in clinic. Apoptotic and non‐apoptotic cell death mediate its cardiotoxicity; however, the underlying non‐apoptotic cell death induced by maduramicin remains unclear. In current study, a recently described non‐apoptotic cell death "methuosis" caused by maduramicin was defined in mammalian cells. Rat myocardial cell H9c2 was used as an in vitro model, showing excessively cytoplasmic vacuolization upon maduramicin (0.0625–5 μg/mL) exposure for 24 h. Maduramicin‐induced reversible cytoplasmic vacuolization of H9c2 cells in a time‐ and concentration‐dependent manner. The vacuoles induced by maduramicin were phase lucent with single membrane and were not derived from the swelling of organelles such as mitochondria, endoplasmic reticulum, lysosome, and Golgi apparatus. Furthermore, maduramicin‐induced cytoplasmic vacuoles are generated from micropinocytosis, which was demonstrated by internalization of extracellular fluid‐phase marker Dextran‐Alexa Fluor 488 into H9c2 cells. Intriguingly, these cytoplasmic vacuoles acquired some characteristics of late endosomes and lysosomes rather than early endosomes and autophagosomes. Vacuolar H + ‐ATPase inhibitor bafilomycin A1 efficiently prevented the generation of cytoplasmic vacuoles and decreased the cytotoxicity of H9c2 cells triggered by maduramicin. Mechanism studying indicated that maduramicin activated H‐Ras‐Rac1 signaling pathway at both mRNA and protein levels. However, the pharmacological inhibition and siRNA knockdown of Rac1 rescued maduramicin‐induced cytotoxicity of H9c2 cells but did not alleviate cytoplasmic vacuolization. Based on these findings, maduramicin induces methuosis in H9c2 cells via Rac‐1 signaling‐independent seriously cytoplasmic vacuolization. Abstract : Maduramicin frequently induces severe cardiotoxicity in animals via apoptotic and non‐apoptotic cell death, however, the underlying mechanism of non‐apoptosis remains unclear. In this study, a recently described non‐apoptotic cell death 'methuosis' caused by maduramicin was defined in mammalian cells. Maduramicin induces cytotoxicity of H9c2 cells via Rac1‐independent methuosis. Rac1 plays a key role of maduramicin‐triggered cell death rather than cytoplasmic vacuolization. Simultaneous manipulation of Rac1 and methuosis will be a potential effectively way to attenuate the cardiotoxicity induced by maduramicin.